The Socially Responsible Organization Lessons from COVID - Mitroff, Ian I.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book explores the nature of the socially responsible organization, specifically the role of crisis management in creating a socially responsible organization. It applies the Myers-Briggs Personality Typology (MBPTI) and the Thomas-Kilmann Conflict Framework to issues such as responses to the COVID-19 pandemic, regulation of tech companies, and infrastructure. Dr. Mitroff lists the major arguments given in regards to these issues and subjects them to the strongest possible scrutiny and critique to hold both individuals and organizations accountable to the larger responsibilities we share as global citizens. This is an open access book.
Chapter 1: The Assault on Reason - The Major Arguments in Defense of not Getting Vaccinated for Covid 19 -- Chapter 2: The Assault on Reason, Part Two - A Deeper Analysis -- Chapter 3: Infrastructure Wars - The Politicization of Everything -- Chapter 4: Regulating Tech Is Only Half the Job -- Chapter 5: The Socially Responsible Organization -- Chapter 6: Dis Versus Mis-Information - Unexpected Insights from Covid19 -- Chapter 7: Compromise Is Key to Our Learning to Live Together - The Resolution of Issues Is Not Possible Without It -- Chapter 8: Coping with a Complex Messy World - Education for the 21st Century and Beyond.
Keywords: Strategic planning; Leadership; Psychology, Industrial; Industrial organization; Business ethics; Business Strategy and Leadership; Organizational Psychology; Organization; Business Ethics